Influence of Vehicle Body Deformation on Vehicle Interior Pressure under Tunnel Pressure Based on Fluid-solid Coupling - Yongping FENG; Chunjun CHEN; Rentao CHEN (机车电传动)
When the high-speed train passes through a tunnel, the tunnel pressure wave will induce the pressure variation inside coach by causing the shape deformation of the train and the air exchange via sealing gaps and the ventilation ducts, and result in the discomfort to the passengers. In order to investigate the pressure fl uctuation caused by the deformation of vehicle body structure, the completely sealed model of vehicle body and carriage structure was built. Based on the STAR-CCM+/Co-Simulations module, the vibration displacement, the amplitude and the change rates of pressure inside coach of high-speed train passing through the tunnel at 350 km/h were calculated by simulation and compared with the theoretical numerical simulation of gas state equation. The results showed that: The largest vibration displacement occurred in the door; The error of the 2 numerical simulation methods based on the fl uid-solid coupling model and the ideal gas state equation was 16.8%, which veri fi ed the reliability of the calculated results; The pressure inside coach was inversely proportional to the coach volume; The maximum negative pressure inside coach was less than 195.3 Pa, and the 3-second change rate of interior pressure was less than 203.1 Pa /(3 s), while the 1-second change rate of interior pressure was less than 149.6 Pa /s, which met the comfort requirements. It could also be helpful to establish the mathematical model of vehicle body under the interaction of multi-factor coupling.